TALEN-mediated functional correction of human iPSC-derived macrophages in context of hereditary pulmonary alveolar proteinosis. Issue 1 (December 2017) - Kuhn, Alexandra; Ackermann, Mania; Mussolino, Claudio; Cathomen, Toni; Lachmann, Nico; Moritz, Thomas
Abstract Hereditary pulmonary alveolar proteinosis (herPAP) constitutes a rare, life threatening lung disease characterized by the inability of alveolar macrophages to clear the alveolar airspaces from surfactant phospholipids. On a molecular level, the disorder is defined by a defect in theCSF2RA gene coding for the GM-CSF receptor alpha-chain (CD116). As therapeutic options are limited, we currently pursue a cell and gene therapy approach aiming for the intrapulmonary transplantation of gene-corrected macrophages derived from herPAP-specific induced pluripotent stem cells (herPAP-iPSC) employing transcriptional activator-like effector nucleases (TALENs). Targeted insertion of a codon-optimizedCSF2RA -cDNA driven by the hybrid cytomegalovirus (CMV) early enhancer/chicken beta actin (CAG) promoter into theAAVS1 locus resulted in robust expression of theCSF2RA gene in gene-edited herPAP-iPSCs as well as thereof derived macrophages. These macrophages displayed typical morphology, surface phenotype, phagocytic and secretory activity, as well as functionalCSF2RA expression verified by STAT5 phosphorylation and GM-CSF uptake studies. Thus, our study provides a proof-of-concept, that TALEN-mediated integration of theCSF2RA gene into theAAVS1 safe harbor locus in patient-specific iPSCs represents an efficient strategy to generate functionally corrected monocytes/macrophages, which in the future may serve as a source for an autologous cell-based gene therapy for the treatment of herPAP.